2015
DOI: 10.1021/ja510387y
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Active Site Guanine in the glmS Ribozyme Self-Cleavage Mechanism: Quantum Mechanical/Molecular Mechanical Free Energy Simulations

Abstract: The glmS ribozyme catalyzes a self-cleavage reaction at the phosphodiester bond between residues A-1 and G1. This reaction is thought to occur by an acid–base mechanism involving the glucosamine-6-phosphate cofactor and G40 residue. Herein quantum mechanical/molecular mechanical free energy simulations and pKa calculations, as well as experimental measurements of the rate constant for self-cleavage, are utilized to elucidate the mechanism, particularly the role of G40. Our calculations suggest that an external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 83 publications
3
84
2
Order By: Relevance
“…66 Both the reaction mechanism and the estimated barrier are consistent with our findings. Note that, although both QM/MM studies are based on similar DFT descriptions of the QM core, they differ methodologically in many significant aspects (see the discussion above) and use distinct starting structures.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…66 Both the reaction mechanism and the estimated barrier are consistent with our findings. Note that, although both QM/MM studies are based on similar DFT descriptions of the QM core, they differ methodologically in many significant aspects (see the discussion above) and use distinct starting structures.…”
Section: Discussionsupporting
confidence: 90%
“…This includes the thermodynamics correction for the rare protonation states of G40 and GlcN6P, and a correction for the systematic error associated with the over-polarization in the minimal QM region with electronic embedding (see Methods, Table 2, Figure 2 and Supporting Information). This estimated range is higher than the barrier derived from the experimentally measured k cat of ~93 min −1 at 30 mM MgCl 2 , corresponding to a free energy barrier of 17.3 kcal/mol at 298 K. 26 Notably, while our paper was under revision, another study reported a kinetic measurement at 3 mM MgCl 2 of a k cat of 0.013 ± 0.003 min −1 , corresponding to a barrier of 22.6 ± 0.2 kcal/mol at 300 K. 66 Hammes-Schiffer et al suggested in this study that 3 mM MgCl 2 is closer both to physiological conditions and to the concentration of divalents in the MD simulations. They thus suggested that the new experimental kinetic constant should be used for comparison with the theoretically calculated barriers.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…For comparison, the pK a values of thymine, uracil, and hypoxanthine moieties located in such oligonucleotides were also determined. The results should be useful for providing estimates for local electric charges of interest in ribozyme mechanisms [27], efficient conversion of dsDNA to ssDNA for nanopore-based DNA sequencing [28], and prediction of differential electrophoretic or chromatographic mobilities of single-stranded oligonucleotides under different pH conditions.…”
Section: Introductionmentioning
confidence: 99%